2003
DOI: 10.1097/01.prs.0000057143.53648.8b
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed and Scanned Carbon Dioxide Laser Resurfacing 2 Years after Treatment: Comparison by Means of Scanning Electron Microscopy

Abstract: Studies have reported short-term and long-term (1-year) findings for laser skin resurfacing. Two of the most popular systems used for this procedure, the continuous-wave Sharplan 40C SilkTouch system and the pulsed Coherent 5000C UltraPulse system with a computer pattern generator, were previously compared for a range of follow-up times up to 1 year, using light microscopy and transmission electron microscopy. This study analyzed the 2-year morphological differences using scanning electron microscopy. Tissue s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…However, in response to Dr Fitzpatrick's comments regarding the CW vs . the flash‐scanned CO 2 , surely the final result is what we are looking for, and as my colleagues and I showed with transmission and scanning electron microscopy, at 2 years postsurgery the continuous wave (CW)‐treated skin was definitely healthier than the flash‐scanned skin 6,7 …”
mentioning
confidence: 98%
“…However, in response to Dr Fitzpatrick's comments regarding the CW vs . the flash‐scanned CO 2 , surely the final result is what we are looking for, and as my colleagues and I showed with transmission and scanning electron microscopy, at 2 years postsurgery the continuous wave (CW)‐treated skin was definitely healthier than the flash‐scanned skin 6,7 …”
mentioning
confidence: 98%
“…Evidence indicates that new collagen synthesis as well as collagen remodeling occurs in response to laser irradiation [15,16]. This does not occur immediately after laser irradiation, but instead occurs over the subsequent days to weeks in response to collagen coagulation [17].…”
Section: Discussionmentioning
confidence: 99%
“…This does not occur immediately after laser irradiation, but instead occurs over the subsequent days to weeks in response to collagen coagulation [17]. Indeed, ongoing changes can occur even up to 2 years after laser treatment [15]. In this study, we only analyzed the acute effects of laser irradiation and so the long-term consequences of this procedure are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…27 Studies in other tissues have shown that there are also delayed effects of laser irradiation on collagen. [28][29][30] In the subsequent days to weeks after irradiation, there is an increase in tissue stiffness as existing collagen remodels and new collagen is synthesized. Ongoing changes can occur even up to 2 yr after laser treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Ongoing changes can occur even up to 2 yr after laser treatment. 28 Increases in tissue stiffness of up to 100% have been shown in tendon connective tissue after laser irradiation. 23 We hypothesized that cochlear laser irradiation would induce delayed changes in basilar membrane collagen similar to that found in other tissues.…”
Section: Introductionmentioning
confidence: 99%